2011
DOI: 10.1161/strokeaha.110.593541
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Hemostatic Therapy in Experimental Warfarin-Associated Intracerebral Hemorrhage

Abstract: Background and Purpose— Intracerebral hemorrhage associated with oral anticoagulants has a poor prognosis. Current treatment guidelines are based on case series and plausibility only, and a common consensus on effective hemostatic therapy is missing. We compared the effectiveness of diverse hemostatic approaches in a mouse model of warfarin-associated intracerebral hemorrhage. Methods— Male C57BL/6 mice received anticoagulant treatment with warfarin (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Moreover, reduction in hematoma expansion achieved with CM352 was accompanied by a substantial improvement in functional and neurological recovery, in marked contrast with clinical trials of rFVIIa, which reduced hematoma growth but did not improve survival or functional outcome after ICH 9. The use of the antifibrinolytic agents ε‐aminocaproic acid and TXA has been proposed after ICH (STOP‐AUST trial)11; however, the only experimental evidence available shows that TXA exacerbates edema in a mouse model of warfarin‐associated ICH 29. Moreover, in contrast with the potential risk for thrombotic events associated with treatment with rFVIIa, ε‐aminocaproic acid, or TXA, we have shown that CM352 does not alter hemostasis 20…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduction in hematoma expansion achieved with CM352 was accompanied by a substantial improvement in functional and neurological recovery, in marked contrast with clinical trials of rFVIIa, which reduced hematoma growth but did not improve survival or functional outcome after ICH 9. The use of the antifibrinolytic agents ε‐aminocaproic acid and TXA has been proposed after ICH (STOP‐AUST trial)11; however, the only experimental evidence available shows that TXA exacerbates edema in a mouse model of warfarin‐associated ICH 29. Moreover, in contrast with the potential risk for thrombotic events associated with treatment with rFVIIa, ε‐aminocaproic acid, or TXA, we have shown that CM352 does not alter hemostasis 20…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomly allocated to 1 of 5 groups: (1) nonanticoagulated control, (2) mice anticoagulated with rivaroxaban, (3) anticoagulated mice receiving PCC (Beriplex P/N 500, 100 U/kg, CSL Behring, Germany), (4) FFP (200 µL, produced by centrifugation of fresh murine blood in EDTA-coated tube at 1500 rpm for 10 minutes, as described), 16 and (5) recombinant FVIIa (Novo Seven, 1 mg/kg, NovoNordisk, Denmark). Groups 1 and 2 received 200 µL saline via the left femoral vein over 5 minutes to match the infused volume of 200 µL for groups 3 to 5 receiving hemostatic/coagulation factors.…”
Section: Effect Of Hemostatic Agents On Hematoma Sizementioning
confidence: 99%
“…[13][14][15] Excess hematoma expansion in this model could be prevented most effectively by infusing prothrombin complex concentrate (PCC), whereas the effect of recombinant human factor factor VIIa (FVIIa) and fresh frozen plasma (FFP) was less consistent. 15,16 Rivaroxaban is another nOAC that directly inhibits the central coagulation factor Xa. Its widespread clinical use beyond stroke prevention in atrial fibrillation is expected because it has been proven effective and safe for additional indications, including acute coronary syndrome and venous thromboembolism.…”
mentioning
confidence: 99%
“…For the entire study, male CD-1 mice aged 12 to 16 weeks were used. Mice were randomly assigned to warfarin or sham treatment, respectively, and were evaluated within the following four study collectives (group sizes defined according to prior studies [11][12][13][14]): (I) hematoma volume measurement (warfarin: n=5, controls: n=5), (II) cell death quantification (warfarin: n=10, controls: n=10), (III) MMP-9 activity determination (warfarin: n=6, controls: n=4), and (IV) perilesional edema measurement (warfarin: n=10, controls: n=10; due to an unexpectedly high mortality rate in the warfarin group, additional mice were randomized in a 2:1 ratio [warfarin: n=13, controls: n=6]). All mice were used for functional outcome determination 24 h after hemorrhage induction.…”
Section: Animalsmentioning
confidence: 99%